Gendered character of barrenness in an African context: An African pastoral study - Magezi E. Baloyi (In die Skriflig, 2017)
The importance of children for African people has been prioritised above many other reasons for marriage. Besides the fact that every childless marriage has only a slim chance of survival, women are the main objects of this pressure. Some African researchers have revealed that it is usually women who are traditionally held responsible for childlessness. It becomes evident when a man takes a second wife without first seeking medical proof of his wife’s barrenness. In other instances, suspicions force men to divorce women or claim their bride price back as a result of childlessness. Besides being a humiliation for women, it is also a gender inequality issue that deserves theological attention and research to make suggestions and advise on how to reduce or eliminate some practices that promote the subjection of women. The purpose of this article is to research how gender inequality and women abuse continue to manifest because of barrenness. A theoretical framework will direct the research methods – the reading of African-based books, articles, newspapers and other relevant media sources will be utilised.